2021
DOI: 10.1016/j.esmoop.2021.100050
|View full text |Cite
|
Sign up to set email alerts
|

A matching-adjusted indirect comparison of combination nivolumab plus ipilimumab with BRAF plus MEK inhibitors for the treatment of BRAF-mutant advanced melanoma☆

Abstract: Background Approved first-line treatments for patients with BRAF V600–mutant advanced melanoma include nivolumab (a programmed cell death protein 1 inhibitor) plus ipilimumab (a cytotoxic T lymphocyte antigen-4 inhibitor; NIVO+IPI) and the BRAF/MEK inhibitors dabrafenib plus trametinib (DAB+TRAM), encorafenib plus binimetinib (ENCO+BINI), and vemurafenib plus cobimetinib (VEM+COBI). Results from prospective randomized clinical trials (RCTs) comparing these treatments hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…8,9 A matching-adjusted indirect comparison demonstrated more favorable overall survival and progression-free survival benefits among patients with BRAF-mutant melanoma treated with nivolumab plus ipilimumab, compared with those treated with targeted therapy combinations, such as dabrafenib plus trametinib. 10 On the other hand, the BRAF/MEK inhibitors may be preferred in patients with rapidly progressing disease and/or symptoms, because BRAF/MEK inhibitors have a shorter time to response compared with checkpoint immunotherapies. In our patient, we selected nivolumab plus ipilimumab because BRAF V600E immunohistochemistry was negative, but nivolumab plus ipilimumab failed to elicit a response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 A matching-adjusted indirect comparison demonstrated more favorable overall survival and progression-free survival benefits among patients with BRAF-mutant melanoma treated with nivolumab plus ipilimumab, compared with those treated with targeted therapy combinations, such as dabrafenib plus trametinib. 10 On the other hand, the BRAF/MEK inhibitors may be preferred in patients with rapidly progressing disease and/or symptoms, because BRAF/MEK inhibitors have a shorter time to response compared with checkpoint immunotherapies. In our patient, we selected nivolumab plus ipilimumab because BRAF V600E immunohistochemistry was negative, but nivolumab plus ipilimumab failed to elicit a response.…”
Section: Discussionmentioning
confidence: 99%
“…These regimens have dramatically improved outcomes in patients with cutaneous melanoma, especially those with BRAF V600‐mutant disease, which constitutes ~50% of metastatic cutaneous melanoma cases 8,9 . A matching‐adjusted indirect comparison demonstrated more favorable overall survival and progression‐free survival benefits among patients with BRAF ‐mutant melanoma treated with nivolumab plus ipilimumab, compared with those treated with targeted therapy combinations, such as dabrafenib plus trametinib 10 . On the other hand, the BRAF/MEK inhibitors may be preferred in patients with rapidly progressing disease and/or symptoms, because BRAF/MEK inhibitors have a shorter time to response compared with checkpoint immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…The association of cobimetinib (a MEK inhibitor) and vemurafenib (a BRAF inhibitor) has been FDA approved as standard treatment for patients with BRAF V600 -mutated melanoma. Clinical data pooled from the BRIM-2, BRIM-3, BRIM-7, and coBRIM studies, involving patients treated with vemurafenib or cobimetinib plus vemurafenib, have demonstrated the combination therapy to be more effective in terms of tumor reduction and progression-free survival, supporting the combination BRAF and MEK inhibition as a standard of care in this disease setting [ 44 ]. Moreover, the association of the BRAF inhibitor dabrafenib (at a dose of 150 mg twice daily) plus the MEK inhibitor trametinib (2 mg once daily) studied in the COMBI-d and COMBI-v trials also showed excellent results leading to long-term benefit in approximately one third of the patients who had unresectable or metastatic melanoma with BRAF V600E or V600K mutation.…”
Section: Methodsmentioning
confidence: 99%
“…Jedoch zeigen Metaanalysen die Überlegenheit der Kombinations-Immuntherapie, gefolgt von der PD-1-Inhibitortherapie gegenüber Dabrafenib/Trametinib, gefolgt von Dabrafenib mono [47] bzw. die Überlegenheit der Kombinations-Immuntherapie gegenüber allen zielgerichteten Kombinationen [48] in Bezug auf PFS und OS. Im Vergleich der Kaplan-Meier-Kurven wird bei den Immuntherapien insbesondere im PFS der frühe steile Abfall der Kurven als Zeichen für primäre Therapieresistenz und das folgende lange Plateau als Zeichen für eine langfristige/anhaltende Krankheitskontrolle deutlich.…”
Section: Zielgerichtete Therapieunclassified